Primary diffuse large B cell lymphoma arising from a leiomyoma of the uterine corpus. Issue 1 (December 2016) - Zhao, Lianhua; Ma, Qiang; Wang, Qiushi; Zeng, Ying; Luo, Qingya; Xiao, Hualiang
Abstract Background Primary diffuse large B cell lymphoma (DLBCL) of the uterus is rare, and primary DLBCL arising from a uterine leiomyoma (collision tumor) has not been reported in the literature. Case presentation We describe the clinical, histological, immunohistochemical, and molecular features of primary DLBCL arising from a leiomyoma in the uterine corpus. A 73-year-old female patient had a uterine mass for 23 years. An ultrasound scan revealed marked enlargement of the uterus, measuring 18.2 × 13 × 16.3 cm, with a 17.6 × 10.9 × 11.6 cm hypoechoic mass in the uterine corpus. The tumors consisted of medium- to large-sized cells exhibiting a diffuse pattern of growth with a well-circumscribed leiomyoma. The neoplastic cells strongly expressed CD79α, CD20 and PAX5. Molecular analyses indicated clonal B-cell receptor gene rearrangement. Conclusions To the best of our knowledge, no previous cases of primary DLBCL arising from a leiomyoma have been reported. It is necessary to differentiate a diagnosis of primary DLBCL arising from a leiomyoma from that of leiomyoma with florid reactive lymphocytic infiltration (lymphoma-like lesion). Careful analysis of clinical, histological, immunophenotypic, and genetic features is required to establish the correct diagnosis.